Expert reviewLeft ventricular to right atrial shunt (Gerbode defect): congenital versus acquired - Yuan, Shi-Min (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Congenital left ventricular to right atrial (LV-RA) shunt (Gerbode defect) is rare, while acquired LV-RA shunt has been increasingly reported. As yet, systematically incorporated data of the LV-RA shunt have not been presented. Aim: To present the clinical features, diagnostic challenge and management strategies of congenital and acquired LV-RA shunts. Material and methods : The data source was based on a comprehensive literature retrieval of the LV-RA shunt in the period 1990–2013. Results : In comparison with the acquired Gerbode defect, the congenital Gerbode defect group of patients were younger and were associated more often with additional congenital disorders. Previous cardiac surgery and infective endocarditis were the two major aetiologies of the occurrence of the acquired shunts. Paravalvular abscess was associated in 10.2% and atrioventricular block in 13.6% of the acquired group patients. Transoesophageal echocardiography showed a higher diagnostic accuracy, lower missed diagnosis and lower inclusive diagnosis rates, in comparison to transthoracic echocardiography, but the misdiagnosis rates of the two modalities did not differ from each other. Four (4.5%) of the acquired group patients were complicated by atrioventricular block following surgical or interventional closure of the shunt. Eight (9.1%) patients died in the acquired group, but no patient died in the congenital group. Conclusions : The diagnosis of an LV-RA shunt is quite challenging, especially in the context of coexisting abnormalities including an additional intracardiac shunt, tricuspid regurgitation, pulmonary artery hypertension and infective endocarditis, which have to be carefully differentiated from the shunt by further investigations. A better control of infective complications and careful manoeuvres during surgery may help to keep the LV-RA-sensitive septum intact.